The Application of Project-Based Teaching Based on Chinese Characteristics in High School Chemistry - Wang, Pengyun; Xu, Suyi; Xu, Ying; Tang, Yanyan (Advances in Social Sciences Research Journal, 2023)
China’s basic education has undergone several reforms, and the new round of curriculum reform has vigorously promoted the policy of "core literacy" and cultivating high-quality talents in all aspects. Project-based teaching is a teaching mode that takes students as the main body and lets students practice in real problem situations. It plays a very important role in promoting students’ problem-solving ability, developing innovative consciousness and implementing "subject core literacy". Based on Chinese characteristics, this paper takes "handmade ancient soap making" as the project theme, disassembles the task, design the teaching process, and briefly describes the application of Chinese project-based teaching in high school chemistry practice teaching